(untitled) (Research, Society and Development, 2021)
This study aimed to measure the efficiency of cinnamon in patients with Type 2 Diabetes Mellitus (DM2), comparing fasting plasma glucose averages and lipid profiles with a placebo group through a meta-analysis. Four databases were the source of the research to find the articles used, including: Medline / PubMed, LILACS and NCBI. 11 randomized clinical trials that evaluated cinnamon on glycemic and lipid parameters were included in this study. Meta-analysis was performed with the aid of the STATA® 16.0 software, which determined the difference in glucose means and lipid profiles compared to a placebo group. Cinnamon at concentrations of 250 mg twice a day decreased blood glucose with MD = -0.25 (95%CI = - 0.36 to -0.14; p<0.00001) and in the intervention with 2 g 3 times a day with MD = -5.60 (95%CI = -6.98 to -4.22; p<0.00001). Total cholesterol was significant with 2 g 3 times a day with MD = 0.98 (95%CI = -1.27 to -0.69), followed by LDL-cholesterol MD = 0.64 (95%CI = 0.88 to 0.40; p<0.00001), and HDL-cholesterol with 500 mg 3 times daily with MD = 0.12 (95%CI = 0.05 to 0.19). High-dose supplementation of cinnamon can reduce glucose and lipid profiles in patients with DM2. This supporting treatment can be useful when added to the diet plan of patients with DM2.